2022
DOI: 10.35848/1347-4065/ac3d0d
|View full text |Cite
|
Sign up to set email alerts
|

Study on chemical synthesis of SnSSe nanosheets and nanocrystals

Abstract: Two kinds of raw material combination for the hot injection method were investigated for the chemical synthesis of SnSSe nanosheets and nanocrystals, which are low-toxic optoelectronic materials. When SnSe quantum dots were synthesized by mainly using oleic acid as Se precursor solvent, the quantum dots changed from spherical to cubic as the size increased. The growth condition dependence of the nanocrystal formation process was discussed. When SnSSe nanocrystals were synthesized by mainly using trioctylphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…We have reported that the Ga 2 O 3 nanowire phase changed from ε-type to β-type at much lower temperature than that known for bulk and thin films without HCl addition. 44 Fig. 7 shows the XRD measurement results of the sample obtained by performing the final dry heat treatment in the temperature range of RT to 900 °C for 60 minutes.…”
Section: Influence Of Heat Treatment On Crystals Of Ga 2 O 3 Nanowiresmentioning
confidence: 99%
“…We have reported that the Ga 2 O 3 nanowire phase changed from ε-type to β-type at much lower temperature than that known for bulk and thin films without HCl addition. 44 Fig. 7 shows the XRD measurement results of the sample obtained by performing the final dry heat treatment in the temperature range of RT to 900 °C for 60 minutes.…”
Section: Influence Of Heat Treatment On Crystals Of Ga 2 O 3 Nanowiresmentioning
confidence: 99%